Heritable arrhythmias associated with abnormal function of cardiac potassium channels. Issue 9 (19th May 2020) - Crotti, Lia; Odening, Katja E; Sanguinetti, Michael C
Abstract: Cardiomyocytes express a surprisingly large number of potassium channel types. The primary physiological functions of the currents conducted by these channels are to maintain the resting membrane potential and mediate action potential repolarization under basal conditions and in response to changes in the concentrations of intracellular sodium, calcium, and ATP/ADP. Here, we review the diversity and functional roles of cardiac potassium channels under normal conditions and how heritable mutations in the genes encoding these channels can lead to distinct arrhythmias. We briefly review atrial fibrillation and J-wave syndromes. For long and short QT syndromes, we describe their genetic basis, clinical manifestation, risk stratification, traditional and novel therapeutic approaches, as well as insights into disease mechanisms provided by animal and cellular models. Graphical Abstract: